Volatile components as chemical markers of the botanical origin of Corsican honeys. (15th September 2017) - Yang, Yin; Battesti, Marie‐José; Costa, Jean; Dupuy, Nathalie; Paolini, Julien
Abstract: In accordance with the national Appellation d'Origine Contrôlée and the European Protected Designation of Origin labels, Corsican honeys can be classified into six ranges (spring, spring maquis, honeydew maquis, chestnut grove, summer maquis and autumn maquis). Toward proposing a new and faster method for performing honey quality assessments, an headspace‐solid phase microextraction (HS‐SPME)/Gas Chromatography (GC)/GC‐Mass Spectrometry (MS) method with multivariate data analysis – principal component analysis (PCA), cluster analysis (CA), partial lest square (PLS) – was developed using 269 Corsican samples, for which the volatile compositions were established a priori . Corsican honeydew and blossom honey could be differentiated by the richness of 3‐furaldehyde in the category of "honeydew maquis". This approach also allowed identification of chemical markers of the botanical origins of blossom honeys, including 2‐aminoacetophenone, p ‐anisaldehyde, 4‐n‐propylanisole, isophorone, and isomers of lilac aldehyde. Therefore, characterization of the volatile fraction of Corsican honeys combined with chemometric analysis may be useful for detecting the nectar contribution of plant species in honeys with complex nectariferous origins. Abstract : A new and faster method for performing honey quality assessments based on HS‐SPME/GC/GC‐MS analysis was developed using 269 Corsican samples. Identification of chemical markers of the botanical origins of blossom honeys was identified, including 2‐aminoacetophenone, p‐anisaldehyde, 4‐n‐propylanisole, isophorone, and isomers of lilac aldehyde. Characterization of the volatile fraction of Corsican honeys combined with chemometric analysis may be useful for detecting the nectar contribution of plant species in honeys.